Pengaruh Good Government Governance Dan Ukuran Legislatif Terhadap Kinerja Pemerintah Daerah - Vegy Gustianra; Vanica Serly (Universitas Negeri Padang, 2019)
The variables tested in the study consist of Good Government Governance measured by the rank of Indonesia Governance Index (IGI) and the size of the legislative by using the number of members of the districs parliament, and also local government performance measured by three proxies, the GDP per capita, Poverty Rates, Independence Ratios, Economic Growth and unemployment rate. The study is conducted in 33 district in Indonesia on 2014. The results show that two is no significant effect of good government governance on local government performance by proxy ofIndependence Ratios and Economic Growth. One is no significant effect on the size of the legislative on the performance of local government by proxy of economic growth. one is significant impact on the size of the legislative on the performance of local government by proxy of Independence Ratiosand three model of studi good government governance and the size of the legislative on the performance of local government by proxy of GDP per capita, Poverty Rates,unemployment rate.